Entorhinal and Transentorhinal Atrophy in Preclinical Alzheimer's Disease - Kulason, Sue; Xu, Eileen; Tward, Daniel J.; Bakker, Arnold; Albert, Marilyn; Younes, Laurent; Miller, Michael I. (Frontiers in Neuroscience, 2020)
This study examines the atrophy patterns in the entorhinal and transentorhinal cortices of subjects that converted from normal cognition to mild cognitive impairment. The regions were manually segmented from 3T MRI, then corrected for variability in boundary definition over time using an automated approach called longitudinal diffeomorphometry. Cortical thickness was calculated by deforming the gray matter-white matter boundary surface to the pial surface using an approach called normal geodesic flow. The surface was parcellated based on four atlases using large deformation diffeomorphic metric mapping. Average cortical thickness was calculated for 1) manually-defined entorhinal cortex, and 2) manually-defined transentorhinal cortex. Group-wise difference analysis was applied to determine where atrophy occurred, and change-point analysis was applied to determine when atrophy started to occur. The results showed that by the time a diagnosis of mild cognitive impairment is made, the transentorhinal cortex and entorhinal cortex was up to 0.6 mm thinner than a control with normal cognition. A change point in atrophy rate was detected in the transentorhinal cortex 9 to 14 years prior to a diagnosis of mild cognitive impairment, and in the entorhinal cortex 8 to 11 years prior. The findings are consistent with autopsy findings that demonstrate neuronal changes in the transentorhinal cortex before the entorhinal cortex.